Measuring localization in the age of economic globalization - Kristina V. Baris; Ma. Charmaine R. Crisostomo; Krizia Anne V. Garay; Christian Regie J. Jabagat; Mahinthan J. Mariasingham; Elyssa Mariel T. Mores (Asian Development Bank (ADB), 2022)
In a highly integrated global economy, linkages of domestic sectors to global trade measure an economy's ability to gain from participating in global value chains. On the other hand, the strength of domestic linkages can provide insights on an economy's cross-industry trade and extent of the localization of economic activity. This paper proposes a measure of domestic linkages based on a value added approach. Using the Asian Development Bank's multiregional input-output table from 2000 and 2007 to 2020, this paper estimates a backward agglomeration index, which measures the extent to which different sectors in the economy source value added from domestic sectors for domestic consumption. An analogous forward agglomeration index, which measures the extent to which domestic sectors absorb value added, is also defined. The combinations of backward and forward agglomeration indexes are consequently used to analyze an economy or a sector's agglomeration status. The agglomeration indexes show a positive correlation with existing reshoring indexes, and a negative correlation with global value chain participation. The indexes are further extended to account for distribution of activities within domestic sectors.
Keywords: D24; D57; F15; O14; 330; agglomeration; value added; globalization; multiregional input-output table; global value chains